Recurrent Autonomic Dysreflexia due to Chronic Aortic Dissection in an Adult Male with Cervical Spinal Cord Injury. (2008) - Vaidyanathan, Subramanian; Hughes, Peter L.; Oo, Tun; Soni, Bakul M.
Abstract : Autonomic dysreflexia is a hypertensive clinical emergency for persons with spinal cord injury at T-6 level or above. Recurrent autonomic dysreflexia is uncommon in spinal cord injury patients and is usually caused by noxious stimuli that cannot be removed promptly, e.g., somatic pain, abdominal distension. A 61-year-old man, who sustained tetraplegia at C-5 (ASIA-A) 38 years ago, was admitted with chest infection. Computerised tomography (CT) of the chest showed the ascending aorta to measure 4 cm in anteroposterior diameter; descending thoracic aorta measured 3.5 cm. No dissection was seen. Normal appearances of abdominal aorta were seen. He was treated with noninvasive ventilation, antibiotics, and diuretics. Nineteen days later, when there was sudden deterioration in his clinical condition, CT of the pulmonary angiogram was performed to rule out pulmonary embolism. This showed no pulmonary embolus, but the upper abdominal aorta showed some dissection with thrombosis of the false lumen. Blood pressure was controlled with perindopril 2 mg, once a day, doxazosin 4 mg, twice a day, and furosemide 20 mg, twice a day. Since this patient did not show clinical features of mesenteric or lower limb ischaemia, the vascular surgeon did not recommend subdiaphragmatic aortic replacement. This patient subsequently developed recurrent episodes of autonomic dysreflexia. Each acute episode of dysreflexia was controlled by nifedipine given sublingually in doses varying from 5 to 20 mg. No inciting cause for autonomic dysreflexia could be found other than chronic aortic dissection. This patient's medication was then changed to doxazosin 8 mg, twice a day, and sustained-release nifedipine 10 mg, twice a day, which helped to prevent recurrent autonomic dysreflexia. Chronic aortic dissection is a very rare cause for recurrent autonomic dysreflexia in ageing spinal cord injury patients. When the inciting cause for dysreflexia is not amenable for treatment, recurrent dysreflexic episodes can be prevented by pharmacotherapy with an alpha-adrenergic blocking agent (doxazosin) and sustained-release nifedipine.